Corrigendum to ’Concentration-dependent transfer and phytotoxicity of iodine and rhenium in lettuce (Lactuca sativa L.) with implications for nuclear waste risk assessment’ [Environ. Pollut. 404 (2026) 128478] - Faraaz Ahmed Mohammad; Sang Rim Kim; Yeon Ju Choi; Mac Cheryl Sulan Charles Emparang; Ji Gu Lee; Min Geon Cho; Dae Geun Jeong; Min Jae Kim; Kyung Min Park; Mi Seon Jeong; Jum Soon Kang (Environmental Pollution, 2026)

Concentration-dependent transfer and phytotoxicity of iodine and rhenium in lettuce (Lactuca sativa L.) with implications for nuclear waste risk assessment - Faraaz Ahmed Mohammad; Sang Rim Kim; Yeon Ju Choi; Mac Cheryl Sulan Charles Emparang; Ji Gu Lee; Min Geon Cho; Dae Geun Jeong; Min Jae Kim; Kyung Min Park; Mi Seon Jeong; Jum Soon Kang (Environmental Pollution, 2026)

Exercise attenuates cisplatin-induced anorexia-cachexia via modulation of hypothalamic inflammation and orexigenic signaling - Se Hwan Park; Jeong Rim Ko; Chang Shin Yoon; Nam Mi Park; Maria Victoria Faith V. Garcia; Hyung Kyu Kim; Jin Han (European Journal of Applied Physiology, 2026)

Angelica decursiva (Miq.) Franch. & Sav. extract inhibits UVB-mediated photoaging by regulating MAPK-related inflammatory pathways - Ha-Rim Kim; Seung-Hyeon Lee; Young-Soo Kim; Sang-Nam Kim; Seon-Young Kim; Mi Hee Park (Molecular & Cellular Toxicology, 2025)
Background Ultraviolet (UV)-B radiation negatively impacts skin health by inducing inflammation and accelerating photoaging through increased expression of matrix metalloproteinases (MMPs), collagen degradation, and inhibition of procollagen synthesis. Angelica decursiva (Miq.) Franch. & Sav. has various biological effects, however, the anti-wrinkle effect has not been reported yet. It has been reported that the ingredients have anti-inflammatory and antioxidant. Objectives This study investigated the protective effects of Angelica decursiva (Miq.) Franch. & Sav. extract (ADE) against UVB-induced photoaging in human skin fibroblasts (Hs68). Results ADE was non-toxic at all concentrations, confirming its safety for cosmetic applications. Furthermore, pretreatment with ADE significantly inhibited UVB-induced degradation of type I procollagen and suppressed MMP-1 expression in Hs68 cells. Additionally, abdominal skin exposure to UVB led to a significant increase in MMP-1 levels and accelerated collagen degradation. However, pretreatment with ADE effectively mitigated these effects, reducing MMP-1 expression and preserving collagen integrity. Conclusion These findings suggest that ADE possesses anti-photoaging properties and could serve as a valuable ingredient in skincare formulations aimed at preventing UVB-induced wrinkle formation.

Potential generation and consumption of carbon dioxide during treatment of mine drainages in South Korea - Duk-Min Kim; Ki-Rim Lee; Mi-Sun Park (Science of The Total Environment, 2025)

Assessing seepage sources of a tailings dump and fractionation of Mo and Zn isotopes - Duk-Min Kim; Dae-Gyu Im; Hye-Lim Kwon; Seong-Taek Yun; Ki-Rim Lee; Mi-Jeong Park; Mi-Sun Park (Science of The Total Environment, 2025)

Anti-melanogenic effect of Moju through inhibition of tyrosinase activity - Ha-Rim Kim; Seung-Hyeon Lee; Eun-Mi Noh; Boung-Jun Oh; Seon-Young Kim; Mi Hee Park (Molecular & Cellular Toxicology, 2024)
Background Moju is a traditional rice beverage local to Jeonju with an alcohol content of 1–2%. Moju is made by boiling makgeolli with several kinds of medicinal herbs, such as ginger, jujube and cinnamon. The raw materials used in Moju are well known for their physiological and functional effects. Although Moju is made with functional raw materials, the operational role of Moju has not yet been reported. Objectives The aim of this study was to identify the anti-melanogenic effects of Moju in B16F10 melanoma cells and explore the potential mechanisms. Results In this study, we investigated the antioxidant activity and anti-melanogenic effect of Moju. Moju showed no toxicity to HEK293T or B16F10 cells. The antioxidant activity of Moju was confirmed by its ability to increase radical scavenging activity. Moju decreased tyrosinase activity in a concentration-dependent manner. At the cellular level, Moju reduced melanin synthesis and the expression of proteins involved in melanin synthesis at concentrations of 100, 250, and 500 μg/mL in B16F10 cells. In addition, Moju inhibited the phosphorylation of extracellular signal-regulated kinase (ERK). Conclusions These results provide evidence that Moju has antioxidant activity and anti-melanogenic effect that occur through regulation of the ERK pathway. Although further research is needed to elucidate the specific mechanism and functional components, the ability of Moju to inhibit melanin synthesis by altering tyrosinase activation suggest that it can be used as a functional whitening ingredient.

Momordica charantia extracts obtained by ultrasound-assisted extraction inhibit the inflammatory pathways - Ha-Rim Kim; Eun-Mi Noh; Seung-Hyeon Lee; Saerom Lee; Dong Hee Kim; Nam Hyouck Lee; Seon-Young Kim; Mi Hee Park (Molecular & Cellular Toxicology, 2024)
Background Momordica charantia is a member of the Cucurbitaceae family and has traditionally been used for medical nutritional therapy to cure diabetes, and its various biological properties have been reported. However, several studies have demonstrated that M. charantia may exert toxic or adverse effects under different conditions. In this study, we prepared an M. charantia extract using ultrasound-assisted extraction, which is a green technology, and verified its anti-inflammatory effects. Objectives The aim of this study was to investigate the anti-inflammatory effects of M. charantia extract using ultrasound-assisted extraction in LPS-induced Raw264.7 macrophages and explore the potential mechanism mediated by the MAPK/NF-κB signaling pathway. Results We found that the M. charantia extract was non-toxic up to a concentration of 500 μg/mL in Raw264.7 cells. We verified that treatment with M. charantia extract significantly reduced the production of nitric oxide and proinflammatory cytokines, including TNF-α, IL-1β, IL-2, and IL-6, in LPS-stimulated RAW264.7 cells. Moreover, the anti-inflammatory cytokine IL-10 was dramatically increased by treatment with the M. charantia extract. In addition, the phosphorylation of the transcription factor NF-κB, which modulates the production of inflammatory proteins, including JNK, ERK, and p38, was reduced by downregulation of the MAPK signaling pathway. Conclusion These results indicate that the M. charantia extract collected using an industrial ultrasonic system is non-toxic and has an anti-inflammatory effect through regulation of the NF-κB and MAPK pathways, suggesting that it can act as a therapeutic candidate for the treatment of inflammatory diseases.

Jageum-Jung, the herbal pharmaceuticals, inhibits the hepatic fibrogenesis as mediated with TGF-β1/smad signaling - Yu Rim Song; Mi Hee Jang; Boyun Jang; Su Jin Bae; Seon Been Bak; Sung Min Lee; Un-Jung Yun; Ju Hee Lee; Sang Mi Park; Dae Hwa Jung; Bok Suk Sa; Jong Kuk Song; et al. (Molecular & Cellular Toxicology, 2022)

Protective effect of oil extracted from Neophocaena asiaeorientalis against hydgrogen peroxide-induced oxidative stress in HepG2 cells - Hye Ryeong Kim; Ji Eun Kim; Woo Bin Yun; Mi Rim Lee; Jun Young Choi; Jin Ju Park; Bo Ram Song; Hyun Keun Song; Dae Youn Hwang (Fisheries Science, 2019)

Isolation and characterization of a novel glycosyl hydrolase family 74 (GH74) cellulase from the black goat rumen metagenomic library - Yun-Hee Song; Kyung-Tai Lee; Jin-Young Baek; Min-Ju Kim; Mi-Ra Kwon; Young-Joo Kim; Mi-Rim Park; Haesu Ko; Jin-Sung Lee; Keun-Sung Kim (Folia Microbiologica, 2017)

Diagnostic usefulness of the GenoType MTBDR plus assay for detecting drug-resistant tuberculosis using AFB smear-negative specimens with positive TB-PCR result - Young Seok Lee; Hye-Rim Kang; Si-Hyeong Lee; Yunmi Kim; Mi-Yeong Kim; Jeong Hwan Shin; Jae Young Moon; Hyun-Kyung Lee; So Young Park; Eun-Kyung Mo; Yong Bum Park; Soo-Yoon Moon; et al. (Infectious Diseases, 2016)